Keterampilan Berkomunikasi Sosial Mahasiswa Pendidikan IPS UPI Pasca Mengikuti Program MSIB - Fauziah, Irma Nur (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2024)
This research focuses on the social competencies possessed by UPI Social Sciences Education students and to discover the condition and development of social communication skills after participating in the MSIB program. Research data was obtained using questionnaires, interviews and documentation methods. The research was carried out at the Faculty of Social Sciences Education, Social Sciences Education Study Program at the Indonesian University of Education, with informants from the UPI MSIB Coordinator and UPI Social Sciences Education Students who had participated in the MSIB program. The results of the research show that there are developments and benefits felt by UPI Social Sciences Education students in improving communication skills which is the main requirement in social interaction to establish relationships with other fellow students and has a good impact in developing student competencies in communication, technology and social skills. while participating in the MSIB program. So, students feel a positive impact after participating in the program. Students feel more confident and disciplined in managing time for themselves than before joining the MSIB program. Although in implementation, students must be ready to adapt to several technical changes in the Independent Campus program policy process determined by the Ministry of Education and Culture.